background image

Theorem 16.27.

Let

v

. If

f

j

h

i

f

x

g

!

"

Ob

f

y

g

then xlim

x

f

=

(

y

)

.

Proof.

im

f

j

h

i

f

x

g

vh

i

f

y

g

;

h

f

ih

i

f

x

g v h

i

f

y

g

;

f

j

h

i

f

x

g

w

(

h

i

f

y

FCD

h

i

f

y

g

)

f

j

h

i

f

x

g

=

h

(

f

j

h

i

f

x

g

)

¡

1

ih

i

f

y

FCD

h

i

f

y

g

=

id

h

i

f

x

g

FCD

f

¡

1

h

i

f

y

FCD

h

i

f

y

g w

id

h

i

f

x

g

FCD

f

¡

1

h

f

ih

i

f

x

FCD

h

i

f

y

g

=

id

h

i

f

x

g

FCD

h

f

¡

1

f

ih

i

f

x

FCD

h

i

f

y

g w

id

h

i

f

x

g

FCD

id

h

i

f

x

g

FCD

h

i

f

x

FCD

h

i

f

y

g

=

h

i

f

x

FCD

h

i

f

y

g

:

On the other hand,

f

j

h

i

f

x

g

vh

i

f

x

FCD

h

i

f

y

g

;

f

j

h

i

f

x

g

vh

i

f

x

FCD

h

ih

i

f

y

g v h

i

f

x

FCD

h

i

f

y

g

.

So

f

j

h

i

f

x

g

=

h

i

f

x

FCD

h

i

f

y

g

.

xlim

x

f

=

f

f

j

h

i

f

x

g

"

r

j

r

2

G

g

=

f

(

h

i

f

x

FCD

h

i

f

y

g

)

 "

r

j

r

2

G

g

=

(

y

)

.

Corollary 16.28.

If lim

h

i

f

x

g

f

=

y

then xlim

x

f

=

(

y

)

.

We have injective

if

h

i

f

y

1

g u h

i

f

y

2

g

= 0

F

(

Ob

)

for every distinct

y

1

; y

2

2

Ob

that is if

is

T

2

-separable.

202

Convergence of funcoids